2019
DOI: 10.1589/jpts.31.790
|View full text |Cite
|
Sign up to set email alerts
|

Efficacies of ultrasound and a handheld dynamometer to predict one-repetition maximum

Abstract: [Purpose] It is important to accurately measure one-repetition maximum to determine the training load and number of repetitions. However, huge and expensive equipment, such as a torque machine and/or dynamometer, is needed to measure one-repetition maximum. Therefore, a more accessible and affordable method has been developed to predict one-repetition maximum. In this study, we aimed to investigate whether one-repetition maximum of the knee extensor could be predicted more accurately with a combination of musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
(29 reference statements)
2
6
0
Order By: Relevance
“…Our results showed a significant relationship between 1RM and MVIC, muscle thickness and thigh circumference for community-dwelling older population, consistent with previous reports on young healthy adults 9 , 10 , 11 ) . Although MVIC measurement is a static muscle strength measurement by isometric contraction, 1RM is a dynamic muscle strength measurement with joint movement, and the MVIC and 1RM measurements are different contraction modes.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results showed a significant relationship between 1RM and MVIC, muscle thickness and thigh circumference for community-dwelling older population, consistent with previous reports on young healthy adults 9 , 10 , 11 ) . Although MVIC measurement is a static muscle strength measurement by isometric contraction, 1RM is a dynamic muscle strength measurement with joint movement, and the MVIC and 1RM measurements are different contraction modes.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the results of stepwise regression analysis revealed that MVIC, age, gender, and thigh circumference at 15 cm above the patella were significant and independent determinants for 1RM estimation (R 2 =0.868). These results expand on the findings of the previous studies for investigating the relationship of 1RM and MVIC for young healthy adults 9 , 10 , 11 ) . The reason why the thigh circumference was extracted significantly without extracting muscle thickness was to measure only the muscle thickness of refutes femoris and vastus immedialis in the knee extensor muscle group.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations